Drivers and outcomes of a shopper-retailer's app relationship - Allam K. Abu Farha (18061042) (2024)
Drawing on the theory of consumption values, consumer-brand relationship paradigm and “lovemark” notion, the reported research offers insights into the role of retail apps in cultivating meaningful relationships with mobile shoppers. The storyline of this research is that a strong shopper-retailer's app relationship is manifested by app respect and app love, which in turn, yield active app-supportive behaviors such as app evangelism and app defense. Both app respect and app love underpin shoppers' perceptions of an array of utilitarian- and hedonic-laden values derived from shopping apps. Data collected in retail fashion apps' settings lend support to the proposed model. App respect is more derived from the app's utilitarian-laden values, whereas app love is more derived from the app's hedonic-laden values. More specifically, functional and epistemic values, as utilitarian-laden values, generate app respect. Conditional, emotional, and social values, as hedonic-charged values, yield app love. Furthermore, app respect and app love generate distinct retailer's app relational outcomes; while app respect influences app defense, app love has more influence on app evangelism. The paper discusses the theoretical and managerial implications of the findings and offers directions for future research. Other Information Published in: Journal of Retailing and Consumer Services License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jretconser.2024.104002